Enzymes Produced by a Pseudomonas Species Which Inactivate Inhibitors of Certain Viral Hemagglutinins. I. Identification and Purification of a Proteinase and Phospholipase C - Schmidt, Nathalie J. (1969)
Filtrates from cultures of a psychrophilic Pseudomonas species, which inactivate serum inhibitors of certain viral hemagglutinins, were shown to contain both lecithinase (phospholipase C) and a proteolytic enzyme with elastase activity. The bacterium was cultivated under conditions favoring production of the respective enzymes, and the enzymes were purified by ammonium sulfate precipitation followed by column chromatography or by gel filtration. The elastase was obtained in crystalline form and was recrystallized. It has properties similar to those of a number of other bacterial elastases but is more heat-labile than most. Although a high degree of purification was achieved for the lecithinase, as evidenced by an increase in specific activity, it was not obtained in crystalline form. Partially purified preparations of the lecithinase had extremely high activity compared to that of commercial preparations of phospholipase C from Clostridium welchii.